Статистичний аналіз тенденцій в промислових міжрегіональних диспропорціях - Аксьонова, Ірина Вікторівна (My University, 2024)
Сучасний розвиток країни та її регіонів характеризується наявністю диспропорцій між рівнями розвитку різних видів економічної діяльності, серед яких значну питому вагу займає промислова галузь. Стаття спрямована на проведення аналізу галузевої структури економіки загалом та промисловості зокрема, визначення диспропорцій в промисловому розвитку за регіонами країни. В статті розглянуто динамічні зміни в розвитку промисловості країни та її регіонів на підставі аналізу обсягу реалізованої промислової продукції на душу населення. Для оцінювання рівня диспропорційності застосовано коефіцієнт варіації, за значенням якого здійснено висновок щодо ступеня коливань у співвідношенні показників, які характеризують промисловість. Проведено аналіз нерівномірності та виявлено тенденції в промисловому розвитку регіонів. Оцінено поляризацію промисловості серед регіонів країни на основі розрахунку коефіцієнтів локалізації. В результаті проведеного дослідження доведено, що сучасний рівень промислового розвитку регіонів країни характеризується диспропорціями в промислової діяльності, що потребує розроблення відповідної регіональної політики.

The modern development of the country and its regions is characterized by the presence of disproportions between the levels of development of various types of economic activity, among which the industrial sector occupies a significant specific weight. Since the development of each sector of the economy is an important part of the economy as a system, solving the problem of structural changes between the components of this system requires constant monitoring and research. The purpose of the article is to analyze the sectoral structure of the economy in general and industry in particular, to determine disparities in industrial development by region of the country. The methodological and informational basis of the research were the works of scientists, which highlight the problems of disproportional development of regions, in particular the industrial sphere, materials of periodicals, Internet resources on the specified issues. During the research, a system-logical approach, a method of summarizing information, statistical methods of structural-dynamic analysis, variation indicators, localization coefficients, a grouping method, and visual analysis were used. The article examines the dynamics of industrial development by region of the country based on the analysis of the volume of industrial products sold per capita. To assess the level of disproportionality of the development of the industrial sector, the coefficient of variation was used, based on the value of which a conclusion was made about the degree of fluctuations in the ratio of indicators characterizing the industry. The analysis of unevenness was carried out and the trends of the industrial development of the regions were determined based on the ratio of the maximum and minimum values of the industry indicators. Based on the calculation of the localization coefficients, the polarization of the industry between the regions of the country was estimated. The practical significance of the conducted research consists in determining the presence of disproportional divergent changes in the industrial development of regions based on the selection of groups of regions depending on the number of people employed in the industrial sphere. As a result of the conducted research, it was proved that the current level of industrial development of the country's regions is characterized by disproportions in industrial activity, which requires the development of an appropriate regional policy taking into account modern influencing factors.
Monitoring as a modern information support for analytics and enterprise management
Keywords: промисловість; диспропорційний розвиток; тенденція; промисловий розвиток; дивергентні зміни; статистичні методи; monitoring system; diagnostics; key performance indicators; information and analytical support; management decision-making system